A Trionychidae (Reptilia: Testudines, Cryptodira) from the Pliocene of Costa Rica, Southern Central America - Laurito, César (2005)
Fossil remains of soft-shelled turtles, Trionychidae, are recorded from the Pliocene fluvial sediments of Costa Rica. This is the first record of the trionychids from the Neotropical lands of Central America. These fossils revealed new faunal elements involved in the American Biotic Interchange, and permit a better knowledge of the evolution and composition of our paleoherpetofauna.